Drought Risk Management in Reflect Changing of Meteorological Conditions (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Droughts are one of the main extreme meteorological, and hydrological phenomena, which influence both the functioning of ecosystems, and many important sectors of human economic activity. Throughout the world, various direct changes in meteorological, and climatic conditions, such as: air temperature, humidity, and evapotranspiration can be observed. They have a significant influence upon the shaping of the phenomenon of drought. Land cover and land use can also be indirect factors influencing evapotranspiration, and, by the same token, the water balance in the water catchment area. They can also influence the course of the process of the drought. The observed climate change, manifested mainly by increases in temperature, in turn, influencing evapotranspiration, may cause intensification in terms of both the degree and frequency of droughts. Droughts related to changes in the hydrological regime, and to the decrease in water resources. Its results can be observed in various sectors, related, among others, to a demand for water for people, agriculture and the Industry. It can also prove problematic for water ecosystems. To reflect the aforementioned information, a reasonable drought risk management is indispensable in order to ease the water demand related problems in various sectors of human activity. This book presents original research on various drought indicators, modern measurement techniques used, among others, for monitoring and predicting droughts, drought indicator trends, the impact of insufficient precipitation on human activity in the context of climate change, and examples of modern solutions devised to prevent water shortages.